Pendekatan Pragmatik Novel Asriaci “Melodylan” - Bangun, Chelsy; Anggereni, Theresia; Naibaho, Jessica; Yuhdi, Achmad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to analyze parts of the novel